The Information Needs of Breast Cancer Patients at All Stages of Their Journey: A Protocol of Scoping Review - Priambodo, Ayu Prawesti; Trisyani, Yanny; Anna, Anastasia; Nuraeni, Aan; Oktafianti, Mutiara Annisa; Sugiharto, Firman; Pebianti, Ranti; Andrianthi, Salsyah (Padjadjaran Acute Care Nursing Journal, 2025)
Breast cancer is the most commonly diagnosed cancer and the leading cause of cancer death in women, therefore breast cancer is the most common cancer in women in most countries. Providing adequate information needed by patients can reduce anxiety and feelings of insecurity. Most of women with breast cancer stated that the information obtained was unsatisfactory. However, few studies have comprehensively addressed the information needs of women with breast cancer across all stages of the disease. This scoping review aimed to fully understand the unique information needs of breast cancer patients at various stages of the cancer continuum. A scoping review will be conducted following PRISMA guidelines. Relevant studies will be identified from databases such as PubMed, Scopus, and Taylor & Francis, EBSCOhost, and ScienceDirect. In addition, searches via Google Scholar, interpersonal network recommendations, and reference chains will also be conducted. Studies will be selected based on PCC criteria, focusing on breast cancer patients as the population, information needs as content, and at various stages of the cancer continuum as the context. Data extraction and risk of bias assessment will be performed using Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) Checklist. This review is expected to provide comprehensive information needs of breast cancer patients at various stages of the cancer continuum. The findings will be valuable for educational institutions, healthcare facilities, in designing innovative, technology-based educating programs that enhance knowledge retention, practical skills, and psychological preparedness.